2021
DOI: 10.3389/frsen.2021.730238
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Mangrove Zonation Mapping Workflow Using Sentinel 2-Derived Indices and Biophysical Dataset

Abstract: Moderate to high resolution satellite imageries are commonly used in mapping mangrove cover from local to global scales. In addition to extent information, studies such as mangrove composition, ecology, and distribution analysis require further information on mangrove zonation. Mangrove zonation refers to unique sections within a mangrove forest being dominated by a similar family, genus, or species. This can be observed both in natural and planted mangrove forests. In this study, a mapping workflow was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Species belonging to Acanthaceae and Lythraceae were found abundantly in the sea fringing zone. Genera from these families, such as Avicennia and Sonneratia, were more diverse and dominant in the sea fringing zone as other studies also mentioned the same result (Liu et al 2018;Nasrin et al 2020;Baloloy et al 2021). The areas are characterized as having high saline levels and exposed to waves.…”
Section: Mangrove Distribution and Its Relationship With Altitudementioning
confidence: 62%
See 1 more Smart Citation
“…Species belonging to Acanthaceae and Lythraceae were found abundantly in the sea fringing zone. Genera from these families, such as Avicennia and Sonneratia, were more diverse and dominant in the sea fringing zone as other studies also mentioned the same result (Liu et al 2018;Nasrin et al 2020;Baloloy et al 2021). The areas are characterized as having high saline levels and exposed to waves.…”
Section: Mangrove Distribution and Its Relationship With Altitudementioning
confidence: 62%
“…We applied elevation as an independent variable to explain its relationship with the distribution of mangroves (Matthijs et al 1999;Fu et al 2018;Baloloy et al 2021). We found that the distribution of some mangrove families is likely affected by altitude which grows dominantly either in the sea fringing zone or the landward zone, while other families grow randomly in terms of elevation.…”
Section: Mangrove Distribution and Its Relationship With Altitudementioning
confidence: 99%
“…Of these, the outwelling of DIC to the ocean is considered the most important (Maher et al, 2018;Reithmaier et al, 2023). The area of mangroves in the Fukido River estuary was estimated to be 20.04 ha (Baloloy et al, 2021). By combining the reported values of each flux with the results of this study, we investigated the fate of sequestered carbon in the Fukido River mangrove forest.…”
Section: Controlling Factors Of Pco2 In Water Over the Spring-neap (L...mentioning
confidence: 98%
“…Rainfall is relatively abundant during the rainy season from May to June, and during the typhoon season from August to September (approximately 43% of the annual rainfall). A mangrove forest is dominated by Bruguiera gymnorrhiza and Rhizophora stylosa and is distributed over approximately 20.04 ha (Baloloy et al, 2021). The mangrove forest is considered mature; the maximum tree heights of B.gymnorrhiza and R.stylosa are 13.2 m and 11.6 m, respectively (Ohtsuka et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…Despite data on mangrove extent in some areas of Panay Island, there's a critical deficiency in updated and accurate information on large-scale mangrove cover change over time [5]. To address this urgent need to understand the status of mangroves and the drivers of their forest loss and gain, rapid and accurate extent mapping must be done [6]. By harnessing the power of satellite technology as well as artificial intelligence, these ecosystems can be managed more effectively.…”
Section: Introductionmentioning
confidence: 99%